EPIDEMIOLOGIC OVERVIEW OF AIDS IN BRAZIL - Annah Rachel Graciano; Priscilla dos Santos Decembre Montalvão; Lucas Mike Naves Silva; Cristiana Marinho de Jesus França (UniEVANGÉLICA, 2016)
Objective: To verify the prevalence of AIDS in Brazil among the years 2000 and 2014 and the mortality rate from 2000 to 2013, correlating the rates for male and female and age. Methods: analytical ecological study with temporal bias of design. The data sources used were SIH, SIM and IBGE. The quantified variables refer to the gender and age of the general population. The selected groups were aged between 0 and 100 years of age. Results: The study showed that between 2000 and 2014 there was a significant reduction in the prevalence of AIDS in Brazil. Regarding the findings by gender, the highest overall prevalence rate corresponded to the year 2001 with a rate of 0.027% (95% CI: 0.027% - 0.028%), while the lowest rate was for the year 2014 with the corresponding rate of 0.010% (95% CI: 0.010% - 0.010%). Regarding the number of cases relating to age, there was a significant reduction in the absolute number of cases among the 2005 and 2006 and subsequent increase between 2006 and 2007. Conclusion: It was concluded that the AIDS epidemiological patterns in Brazil over the the last 15 years was favorable, with significant decrease from 2000 to 2014 while mortality rates not having be changed during the period analyzed.